GAMBARAN PENGETAHUAN IBU HAMIL TENTANG ASI EKSKLUSIF - Siahaan, Vera Renta (MIDWIFERY JOURNAL, 2021)
Background of this research is that breast milk is the best food for babies because it contains the most suitable nutrients for infant growth and development. Until now, there are still very few mothers who provide exclusive breastfeeding for six months and make two years with complementary foods (complementary foods). (Ministry of Health, 2014) According to data from the Ministry of Health, the national breastfeeding rate, the coverage of infants who are exclusively breastfed is 61.33%. This figure is also relatively small considering the importance of breastfeeding in children's lives.Purpose  was to describe the knowledge of mothers about exclusive breastfeeding in Tanjung Tongah Village, Pematangsiantar City.Method is descriptive with a cross-sectional design. The analysis used univariate analysis to describe knowledge. The study population was pregnant women in the third trimester of Tanjung Tongah Village. The research sample of the entire population of pregnant women in Tanjung Tongah Village in the third trimester of April to October 2019 was 45 respondents. The instrument used was a questionnaire of knowledge about exclusive breastfeedingThe results showed that most of the 26 respondents (57.8%) had less knowledge about exclusive breastfeeding. And almost half of respondents 19 respondents (42.2%) had good knowledge about exclusive breastfeeding. Health workers are expected to increase health promotion activities regarding exclusive breastfeeding so that they are expected to increase the knowledge of mothers about exclusive breastfeeding.Conclusion Most of the respondents, namely 26 respondents (57.8%) had less knowledge about exclusive breastfeeding. And almost half of the 19 respondents (42.2%) have good knowledge about exclusive breastfeeding.Suggestions It is expected that health workers will provide health education regarding exclusive breastfeeding Keywords: Knowledge, Pregnant Women, Exclusive Breastfeeding ABSTRAK Latar belakang penelitian ini adalah ASI merupakan makanan terbaik bagi bayi karena mengandung zat gizi paling sesuai untuk pertumbuhan dan perkembangan bayi. Hingga saat ini, masih sedikit ibu yang memberikan ASI eksklusif selama enam bulan dan dilanjutkan hingga dua tahun dengan makanan pendamping ASI (MPASI). (Kemenkes, 2014)  Menurut data Kementerian Kesehatan angka pemberian ASI secara nasional, cakupan bayi yang mendapat ASI eksklusif sebesar 61,33%. Angka ini juga terbilang kecil jika mengingat pentingnya peran ASI bagi kehidupan anak.Tujuan Penelitian untuk megetahui gambaran pengetahuan ibu tentang ASI eksklusif di Kelurahan Tanjung Tongah Kota Pematangsiantar.Metode penelitian ini deskriptif mengunakan desain cross sectional. Analisis yang digunakan analisa univariat untuk mendeskripsikan pengetahuan. Populasi penelitian ini yaitu ibu hamil di Kelurahan Tanjung Tongah trimester III. Sampel penelitian seluruh populasi ibu hamil di Kelurahan Tanjung Tongah trimester III bulan April sampai dengan bulan Oktober 2019 sebanyak 45 responden. Instrumen yang digunakan kuesioner pengetahuan tentang ASI EksklusifHasil penelitian menunjukkan sebagian besar responden 26 responden (57,8%) memiliki pengetahuan kurang tentang ASI eksklusif. Dan hampir setengahnya responden 19 responden (42,2%) memiliki pengetahuan baik tentang ASI eksklusif. Petugas kesehatan diharapkan dapat meningkatkan kegiatan promosi kesehatan mengenai ASI eksklusif sehingga diharapkan dapat menambah pengetahuan ibu tentang ASI eksklusif.Kesimpulan Sebagian besar responden yaitu 26 responden (57,8%) memiliki pengetahuan kurang tentang ASI eksklusif. Dan hampir setengahnya responden 19 responden (42,2%) memiliki pengetahuan baik tentang ASI eksklusif.Saran Diharapkan kepada petugas kesehatan untuk memberikan penyuluhan kesehatan mengenai ASI Eksklusif Kata Kunci : Pengetahuan, Ibu Hamil, ASI Eksklusif